Aplikasi fosfin formulasi cair terhadap Thrips parvispinus Karny (Thysanoptera: Thripidae) pada bunga potong krisan - Taufan Tanto Setyawan; Idham Sakti Harahap; Dadang Dadang (Perhimpunan Entomologi Indonesia, 2016)
Chrysanthemum (Chrysanthemum indicum) as one of horticultural commodities has a good prospect to be developed as source of country revenue. The export of cut flowers of chrysanthemum from Indonesia tends to increase year by year. However, Thrips parvispinus Karny (Thysanoptera: Thripidae) which is major insect pest of chrysanthemum often attacks this flower in the field until postharvest causing the decrease of quality of flowers. The poor quality of cut flowers of chrysanthemum including the presence of T. parvispinus will be rejected by foreign businesses. Therefore, control measures of this insect pest by quarantine officers are important. Treatment can be done using liquified formulation phosphine fumigant. The objectives of this study were to determine the concentration of liquified formulation phosphine and exposure time which will were effectively kill T. parvispinus and to evaluate the quality of cut flowers of chrysanthemums treated with phosphine fumigant. T. parvispinus was exposed to liquied formulation phosphine at 9 concentrations (0, 25, 50, 75, 100, 125, 150, 175 and 200 ppm) with 3 exposure times (1, 3, and 6 hours). Moreover, validation test of concentration nd exposure time of liquified formulation phosphine on cut flowers of chrysanthemum was conducted to evaluate the quality of chrysanthemum cut flowers of treated with phosphine fumigant. Results showed that liquified formulation of phosphine at concentration of 200 ppm and on 1 hour of exposure time completely killed T. parvispinus by 100% mortality. At 200 ppm and exposure time until 6 hours did not affect the quality of cut flowers of chrysanthemum.